Vaccine induced mastocytoma - Anwar Alramthan; Laila Ashour; Mohammed Alenezi (Wolters Kluwer Medknow Publications, 2022)
Mastocytoma has been reported to appear in close temporal or spatial relationship to intramuscular injection of Hepatitis B vaccine. Here, we report a case of isolated vaccine induced mastocytoma occurring in an 8-month-old female patient.